The formation of the historical world in the human sciences - Dilthey, Wilhelm, 1833-1911.; Makkreel, Rudolf A., 1939-; Rodi, Frithjof, 1930-; Dilthey, Wilhelm, 1833-1911.; American Council of Learned Societies (Princeton, N.J. : Princeton University Press, 2002)
Publisher's description: This volume provides Dilthey's most mature and best formulation of his Critique of Historical Reason. It begins wi th three "Studies Toward the Foundation of the Human Sciences," in whic h Dilthey refashions Husserlian concepts to describe the basic structur es of consciousness relevant to historical understanding. The volume ne xt presents the major 1910 work The Formation of the Historical World i n the Human Sciences. Here Dilthey considers the degree to which carrie rs of history--individuals, cultures, institutions, and communities--ca n be articulated as productive systems capable of generating value and meaning and of realizing purposes. Hegel's idea of objective spirit is reconceived in a more empirical form to designate the medium of commona lity in which historical beings are immersed. Any universal claims abou t history need to be framed within the specific productive systems anal yzed by the various human sciences. Dilthey's drafts for the Continuati on of the Formation contain extensive discussions of the categories mos t important for our knowledge of historical life: meaning, value, purpo se, time, and development. He also examines the contributions of autobi ography to historical understanding and of biography to scientific hist ory. The finest summary of Dilthey's views on hermeneutics can be found in "The Understanding of Other Persons and Their Manifestations of Lif e." Here, Dilthey differentiates understanding relative to three kinds of manifestations of life. After giving his analysis of elementary unde rstanding, he examines the role of induction in higher understanding an d interpretation, and the relevance of transposition and re-experiencin g for grasping individuality.
Includes bibliographical references and index.
Electronic text and image data.
Keywords: Philosophy; History -- Philosophy; Social sciences -- Philosophy